Admiração reverencial e sua ação humanizadora: estudo acerca da desumanização e corporificação das emoções - Espinosa, Ruth Izabel Vasconcelos Lyra Romero (2019)
Through two experiments we investigated dehumanization and the role of positive emotions such as awe in humanization. Dehumanization consists in denying uniquely human (UH) or human nature (HN) characteristics to other individuals. In this sense, the non-attribution of secondary emotions to people outside the group is a way of dehumanizing them, as it brings them closer to animality. Another aspect that may indicate dehumanization is the embodiment of emotions, which we seek to evaluate in experiment 1. Such aspect is a phenomenon that occurs when evaluating where in the body each emotion is perceived and felt. Since the non-attribution of secondary emotions is a way of dehumanizing, it can be inferred that the embodiment of emotions occurs differently when one imagines that this emotion belongs to another person, a typically dehumanized group. In experiment 1, we evaluated 3 embodiment groups - 1) himself, 2) a similar one (student like him), and 3) homeless. They were instructed to respond to the task of Bodily Sensations Maps (BSMs) for eighteen emotions that could be basic (anger, fear, joy) and complex (awe, compassion, pride) considering their own emotions (group 1), peer emotions (group 2) or homeless people emotions (group 3). According to the initial hypotheses, no significant differences were found between the BSMs produced for their own emotions and for the homeless in relation to the basic emotions. However, significant differences were found in complex emotions. A greater degree of similarity was observed between maps produced by self-emotions and those of other students compared to maps produced for homeless people. In experiment 2 we evaluated the impact of positive emotion, awe, as it would have a humanizing role, indicated by the attribution of secondary emotions to homeless people. This emotion was translated to Portuguese in our study, maintaining its main characteristics of being an emotion with aspects of admiration and fear, being elicited before something great that defies understanding. In this study we focus in the positive aspect of this emotion, which promotes admiration, diminishing of the self, reevaluating beliefs and increasing pro-social behaviors. For this experiment, the same 3 embodiment groups produced the BSMs, after neutral emotional modulation, awe and joy. Awe intensified the perception of emotions for the three groups, but had a more intense role in group 3. Similarity analysis indicated results according to the hypothesis that the similarity of group 3 is lower with group 1. These findings made possible to observe implicit dehumanization phenomena that are less subject to deliberate choices, and to look at the possibility of modifying the perception of typically dehumanized groups. Importantly, BSMs have proven to be an interesting tool for addressing how others' emotions are perceived